Language Anxiety and Its Impact on Speaking Fluency: A Psycholinguistic Perspective on EFL Students - Arini, Tria; Amalia, Murni; Siregar, Kevin Alfansyah; Lubis, Yani (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
Language anxiety has become a central focus in understanding the challenges faced by English as a Foreign Language (EFL) students, particularly in speaking activities that require rapid cognitive processing. From a psycholinguistic perspective, anxiety is viewed not only as an emotional reaction but also as a factor that interferes with the mental mechanisms essential for fluent speech production. When learners experience anxiety, their working memory capacity is reduced, making it more difficult to retrieve vocabulary, organize ideas, and construct sentences smoothly in real time. As a result, their speaking fluency is negatively affected, demonstrated through increased hesitations, pauses, self-corrections, and reduced speech rate. Anxiety also heightens self-monitoring, causing learners to focus excessively on potential errors rather than on effective communication. Furthermore, fear of negative evaluation often leads students to avoid speaking tasks, limiting exposure to meaningful interaction and hindering fluency development. Understanding how anxiety disrupts cognitive processing provides important insights for educators in designing supportive, low-stress learning environments. This psycholinguistic perspective highlights the need for instructional strategies that reduce anxiety and promote confidence to improve EFL learners’ oral fluency.